2019
DOI: 10.3390/nu11061423
|View full text |Cite
|
Sign up to set email alerts
|

Fruit and Vegetable Prescriptions for Pediatric Patients Living in Flint, Michigan: A Cross-Sectional Study of Food Security and Dietary Patterns at Baseline

Abstract: Though fruit and vegetable consumption is essential for disease prevention and health maintenance, intake among children fails to meet dietary recommendations. Limited access to and the affordability of fresh produce, particularly among low-income youth, are barriers to adequate intake. To address these challenges, researchers and pediatricians in Flint, Michigan, expanded a successful fruit and vegetable prescription program that provides one $15 prescription for fresh fruits and vegetables to every child at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 63 publications
1
46
0
Order By: Relevance
“…Self-reported data was collected from caregiver-child dyads at baseline and at the 6-month follow-up. Study recruitment and the prescription program are described in full in an earlier article sharing baseline food security and dietary patterns in a subsample exclusively of Flint children [30]. All methods were approved by the Michigan State University Institutional Review Board (Study 00000666, titled "Fruit and Vegetable Prescription Program"), and conducted in accordance with the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-reported data was collected from caregiver-child dyads at baseline and at the 6-month follow-up. Study recruitment and the prescription program are described in full in an earlier article sharing baseline food security and dietary patterns in a subsample exclusively of Flint children [30]. All methods were approved by the Michigan State University Institutional Review Board (Study 00000666, titled "Fruit and Vegetable Prescription Program"), and conducted in accordance with the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
“…The advice to replace 100% juice with whole fruit may be especially challenging for low-income children throughout the US, who are less likely to consume adequate amounts of whole fruit than their higher-income peers [11,24,[27][28][29]. To specifically address barriers to accessing fresh produce, some healthcare practices have introduced fruit and vegetable prescriptions that are written by physicians to exchange for fresh produce [30][31][32][33]. Thus far, no studies have examined whether exposure to pediatric fruit and vegetable prescription programs influence consumption of whole fruit among children.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that fruit and vegetable intake is consistently and positively associated with income [8,41]; therefore, pediatric FVPPs are likely to disproportionately benefit low-income children and adolescents. Previous research in Flint has indicated that poor dietary patterns and food insecurity are pervasive issues among children living in this low-income, urban city [49]. Although the current study did not demonstrate a significant difference in food security scores between caregivers who reported that their child had received a prescription and those who did not, it is important to note that previous research has suggested that pediatric fruit and vegetable prescriptions may be an effective tool to improve dietary habits [12,25] as well as food security among low-income households [12,23].…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, our findings build upon the growing literature on innovative strategies used by healthcare systems to respond to patients' social needs with the goal of advancing health equity. Whether it is providing fruit and vegetable prescriptions for patients experiencing food insecurity 25 , fostering lesbian, gay, bisexual, transgender, and queer (LGBTQ)-friendly services 26 , or adopting immigrant-friendly strategies 7 , it is necessary for healthcare facilities to consider the unique challenges patients experience and serve as places of innovation to better address the needs of communities they serve. Facilities in our sample adopted interventions to protect and welcome immigrant patients without an evidence base, necessitating future iterations to establish best practices.…”
Section: Discussionmentioning
confidence: 99%